Pengaruh Pemadatan Berulang Terhadap Sifat Campuran Aspal CPHMA - Salsabila, Nurul Fadhilah; Nurdin, Abdul Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
Indonesia is one of the countries that have natural wealth on Buton Island, commonly known as Buton Asphalt. One of the products is Cold Paving Hot Mix Asbuton (CPHMA). CPHMA is a natural asphalt mixture consisting of aggregates, buton grains, juvenile substances and other added substances, which are hotly mixed and ready for cold use. CPHMA is widely used on low-traffic roadways. The purpose of this study was to determine the effect of repeated solidification on the properties of near-cold hot mixed smutons (Cold Paving Hot Mix Asbuton) by testing Marshall's method. This study used repeated solidification methods on the 7th, 14th and 21st days. The test items were made of 18 briquettes consisting of 6 characteristic briquettes and 12 variational briquettes. This study refers to the 2018 Bina Marga Specification. Results from this study show that the influence of repeated solidification on CPHMA asphalt mixtures causes density, stability, MQ and VFB to decrease further. The flow, VMA, and VIM values are increasing.